2018
DOI: 10.4236/mri.2018.71002
|View full text |Cite
|
Sign up to set email alerts
|

Some Marker Enzymes and Histological Alteration on the Administration of Tramadol Hydrochloride on Rat Liver

Abstract: The ease of availability and potential tendency to abuse tramadol hydrochloride prompted this research. Making use of biochemical and histological techniques, concentrations of marker enzymes were monitored along with alterations in the liver architecture of wistar albino rats in graded doses of tramadol hydrochloride for 28 days. Specifically, levels of gammaglutamyltransferase (Ɣ-GT), alanine aminotransferase (ALT) and aspartate aminotransferase (AST) were determined. Statistical evaluation of the results at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Several experimental studies indicated that the Reactive Oxygen Species (ROS) production should be considered a TR-induced toxicity mechanism. Therefore, Oxidative Stress (OS) following TR exposure induces toxicity and damage in different organs [11][12][13][14][15]. OS is defined as overproduction and accumulation of free radicals, including ROS in cells and tissues, and the inability of the biological system to detoxify these reactive products.…”
Section: Introductionmentioning
confidence: 99%
“…Several experimental studies indicated that the Reactive Oxygen Species (ROS) production should be considered a TR-induced toxicity mechanism. Therefore, Oxidative Stress (OS) following TR exposure induces toxicity and damage in different organs [11][12][13][14][15]. OS is defined as overproduction and accumulation of free radicals, including ROS in cells and tissues, and the inability of the biological system to detoxify these reactive products.…”
Section: Introductionmentioning
confidence: 99%
“…Tramadol is a centrally acting analgesic drug, used for management of moderate to severe pain in a variety of diseases as osteoarthritis, fibromyalgia, diabetic neuropathy, neuropathic pain, and even perioperative pain in human patients (El-Gaafarawi, 2006); in addition, it is used in the treatment of opiate withdrawal and premature ejaculation (Simeon & Abbey, 2018). Its analgesic effect is due to its partial affinity for the mu-opiate receptor as well as its inhibition of the reuptake of norepinephrine and serotonin (Shadnia et al, 2008).…”
Section: Introductionmentioning
confidence: 99%